Solution‐Processed High‐Performance ZnO Nano‐FETs Fabricated with Direct‐Write Electron‐Beam‐Lithography‐Based Top‐Down Route. (25th January 2021) - Tiwale, Nikhil; Senanayak, Satyaprasad P.; Rubio‐Lara, Juan; Prasad, Abhinav; Aziz, Atif; Alaverdyan, Yury; Welland, Mark E.
Abstract: Zinc oxide (ZnO) has been extensively investigated for use in large‐area electronics; in particular, the solution‐processing routes have shown increasing promise towards low‐cost fabrication. However, top‐down fabrication approaches with nanoscale resolution, towards aggressively scaled device platforms, are still underexplored. This study reports a novel approach of direct‐write electron‐beam lithography (DW‐EBL) of solution precursors as negative tone resists, followed by optimal precursor processing to fabricate micron/nano‐field‐effect transistors (FETs). It is demonstrated that the mobility and current density of ZnO FETs can be increased by two orders of magnitude as the precursor pattern width is decreased from 50 µm to 100 nm. These nano‐FET devices exhibit field‐effect mobility exceeding ≈30 cm 2  V −1  s −1 and on‐state current densities reaching 10 A m −1, the highest reported so far for direct‐write precursor‐patterned nanoscale ZnO FETs. Using atomic force microscopy and parametric modeling, the origin of such device performance improvement is investigated. The findings emphasize the influence of pre‐decomposition nanoscale precursor patterning on the grain morphology evolution in ZnO and, consequently, open up large‐scale integration, and miniaturization opportunities for solution‐processed, high‐performance nanoscale oxide FETs. Abstract : Position‐specific fabrication of zinc oxide (ZnO) micro/nanopatterns is demonstrated using novel top‐down approach of direct‐write electron‐beam lithography of solution precursors. ZnO field‐effect transistors thus fabricated exhibit two orders of mobility enhancement by shrinking the patterned width from microns to 100 nm scale, and reach values exceeding 30 cm 2  V –1  s –1 with on‐state current densities up to 10 A m –1 .